2010
DOI: 10.1186/1752-1947-4-139
|View full text |Cite
|
Sign up to set email alerts
|

Massive variceal bleeding secondary to splenic vein thrombosis successfully treated with splenic artery embolization: a case report

Abstract: IntroductionSplenic vein thrombosis results in localized portal hypertension called sinistral portal hypertension, which may also lead to massive upper gastrointestinal bleeding. Symptomatic sinistral portal hypertension is usually best treated by splenectomy, but interventional radiological techniques are safe and effective alternatives in the management of a massive hemorrhage, particularly in cases that have a high surgical risk.Case presentationWe describe a 23-year-old Greek man with acute massive gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Left‐sided PHT due to splenic vein obstruction is more commonly seen in adults secondary to pancreatic pathologies (i.e. chronic pancreatitis and pancreatic tumor) and is known as sinistral PHT . In adults, emergency SAE has been successfully used to treat acute severe gastric variceal bleeding due to SVT .…”
Section: Discussionmentioning
confidence: 99%
“…Left‐sided PHT due to splenic vein obstruction is more commonly seen in adults secondary to pancreatic pathologies (i.e. chronic pancreatitis and pancreatic tumor) and is known as sinistral PHT . In adults, emergency SAE has been successfully used to treat acute severe gastric variceal bleeding due to SVT .…”
Section: Discussionmentioning
confidence: 99%
“…Bertina reported that Von Leiden factor (FVL) deficiency has been reported in 2% to 30% of patients with portal vein thrombosis [15]. Moreover, the other articles found that FVL deficiency was also highly associated with splenic vein thrombosis [16,17]. As other causes, advanced left renal cancer and myeloproliferative disease are recognized.…”
Section: Pathophysiology/symptoms Of Left-sided Portal Hypertensionmentioning
confidence: 99%
“…Then, the increased blood flow dilates the submucosal veins of stomach, resulting in gastric varices (Figure 1). Because blood drainage is diverted by the coronary vein into the patent portal system, the presence of gastric varices without esophageal varices is a very specific sign of splenic vein occlusion [17]. This condition, which is commonly silent clinically, can cause hypersplenism or gastrointestinal hemorrhage.…”
mentioning
confidence: 99%
“…Some authors have reported that splenic artery embolization (SAE) is an effective alternative to splenectomy for the treatment of gastric variceal bleeding with left-sided portal hypertension [2, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%